2017
DOI: 10.1007/s11837-017-2691-1
|View full text |Cite
|
Sign up to set email alerts
|

Wolframite Conversion in Treating a Mixed Wolframite–Scheelite Concentrate by Sulfuric Acid

Abstract: Complete wolframite conversion in sulfuric acid is significant for expanding the applicability of the sulfuric acid method for producing ammonium paratungstate. In this paper, the conversion of wolframite in treating a mixed wolframite-scheelite concentrate by sulfuric acid was studied systematically. The results show that the conversion of wolframite in sulfuric acid is more difficult than that of scheelite, requiring rigorous reaction conditions. A solid H2WO4 layer forms on the surfaces of the wolframite pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We favor the higher values because thermodynamic calculation result show an accordant trend with the experimental results[26], while the more negative values seem more suited to pyrometallurgical calculations. So we accept, respectively, -1154.8 and -1053.91 kJ• mol -1 for ∆ 298 and ∆ 298 of ferberite in this paper, which was also accepted in the recent research of Martins[28] and Lange's Handbook of Chemistry[32].…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…We favor the higher values because thermodynamic calculation result show an accordant trend with the experimental results[26], while the more negative values seem more suited to pyrometallurgical calculations. So we accept, respectively, -1154.8 and -1053.91 kJ• mol -1 for ∆ 298 and ∆ 298 of ferberite in this paper, which was also accepted in the recent research of Martins[28] and Lange's Handbook of Chemistry[32].…”
mentioning
confidence: 72%
“…Our previous research [26] showed that increasing Fe 2+ in the solution hinders the FeWO4 decomposition, while oxidization of Fe 2+ to Fe 3+ or/and renewing the acid solution by a two-stage decomposition favors FeWO4 reaction. This explains the impact of oxidization by HNO3 in Fig.…”
Section: In Hcl Solutionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Considering discharge of high-salinity wastewater, volatility, and cost, sulfuric acid is an appropriate candidate to decompose scheelite concentrate (Forward and Vizsolyi, 1965), forming solid H2WO4 and CaSO4. In our previous work, the conversion of tungsten concentrate in H2SO4 solutions was systematically studied, including the mechanism of H2WO4 layer formation on unreacted tungsten minerals (Li et al, 2017b;Shen et al, 2018a) and the kinetics of scheelite conversion in sulfuric acid (Shen et al, 2018b). It has been approved that tungsten concentrates can be completely converted in H2SO4 solution under appropriate conditions .…”
Section: Introductionmentioning
confidence: 99%